Homesickness pada Siswa Baru di Pesantren : Bagaimana Peran Self Compassion dan Friendship Quality - Maya Yasmin; Gumi Langerya (Jurnal Ilmu Perilaku, 2022)
Boarding school is one of the oldest educational institutions in Indonesia that’s able to maintain its existence in this modern era. Homesickness is one of the most significant issues faced by students during their transition to boarding. This study aims to investigate the role of self- compassion and friendship quality on homesickness among first year boarding school students, involving 193 students of 7th grade aged 12-13 years in Medan, North Sumatera by using the cluster random sampling technique. Data analysis results by multiple regression explained that self-compassion and friendship quality has a significant effect on homesickness with an effective contribution of 24.9% and 75.1% influenced by other variables not examined in this study. Based on this research, it is concluded that developing self-compassion and friendship quality can help reduce homesickness among first year boarding school students.